Kepribadian Tokoh Topan Sebagai Orang Tua Tunggal Pada Film Tampan Tailor - Siti Lutfiah Rabiyatul Adawiyah (Signifiѐ, 2023)
The research entitled "The Personality of the Character Topan as a Single Parent in the Film Tampan Tailor" aims to describe the personality psychology of the character Topan as a single parent in the film Tampan Tailor and the personality of the character Topan as a single parent in the film Tampan Tailor. This study uses a review of literary psychology Abraham Maslow with an objective approach. Based on the results of data analysis, all the psychological needs of the topan character can be fulfilled, both basic needs, namely physiological and the highest needs, namely self-actualization. The personality of the topan character as a single parent has the characteristics of knowing himself, keeping promises, firm, forgiving, hardworking, efficient, patient, reckless, humorous, and compassionate.